MTMR14 depletion aggravates intrapulmonary inflammation and emphysema in experimental COPD through activating macrophage M1 polarization - Jiaheng Zhang; Yuan Zhan; Zhesong Deng; Shanshan Chen; Ruonan Yang; Yating Zhang; Hao Fu; Qian Huang; Jixing Wu; Yiya Gu; Jungang Xie (Respiratory Research)
Abstract Background Chronic obstructive pulmonary disease (COPD) is typically characterized by chronic airway inflammation and emphysema. Macrophage polarization plays an important role in COPD, while the precise molecules and mechanisms underpinning it have yet to be fully elucidated. Pulmonary decrease of myotubularin-related protein 14 (MTMR14) expression conduces to the progression of COPD in our prior publication, while the further analysis reveals the differential expression of MTMR14 in alveolar macrophages, whose function and related mechanisms are worth further research. Our study aims to investigate the role and mechanism of MTMR14 in macrophages of COPD. Methods The expression and potential role of MTMR14 in COPD macrophages was explored via bioinformatic analysis and clinical detection, as well as in vivo and vitro experiments. By constructing animal model with Mtmr14 knockout and cell model with the knockdown or over-expression of MTMR14, the effect of MTMR14 on polarization direction of macrophages and the related signaling pathways were elaborated. Indirect co-culture was performed to probe the influence of MTMR14 in the crosstalk between macrophages and alveolar epithelium. The regulation of ubiquitin-proteasome system on MTMR14 expression was investigated via (co-)immunoprecipitation and cycloheximide chase assay. Results Based on analysis from open-access single-cell sequencing data, MTMR14 was down-regulated in macrophages of COPD patients, which was confirmed in clinical specimens, animal and cell models. Meanwhile, MTMR14 was functionally enriched in inflammatory response and macrophage activation. Correspondingly, the knockout of MTMR14 aggravated the pulmonary function decline, emphysema, inflammation and pro-inflammatory macrophage polarization in mice exposed by cigarette smoke (CS). Mechanically, MTMR14 negatively regulated the M1 polarization of macrophages under CS extract (CSE)-stimulation through PI3K/Akt and NF-κB pathways. In addition, damage from macrophages on alveolar epithelium was intensified by the down-regulation of MTMR14 in the formation of emphysema. Finally, TRIM21 was found to down-regulate MTMR14 through ubiquitin-proteasome system in CSE-stimulated macrophages. Conclusions Our findings underscore the mitigative role of MTMR14 on macrophage polarization towards pro-inflammatory phenotype, offering a promising target for prevention and intervention for COPD in clinical settings. Clinical trial number Not applicable.